Case Report of Photodynamic Therapy in the Treatment of Dental Caries on Primary Teeth - da Mota, Ana Carolina Costa (J Lasers Med Sci, 2016)
Introduction: The partial removal of dental caries aiming to maintain the integrity of the pulp has been considered the therapy of choice in the treatment of deep carious lesions, as long as certain principles of diagnosis are respected. Dentists are always looking for techniques to remove the decayed tissue with biosafety, what provides more comfort to the patient especially when it comes to children. Photodynamic therapy (PDT) is an antimicrobial treatment. PapacárieMblue is a modification of the regular Papacárie, with a photosensitizer added to it. Case Report: PapacárieMblue was used in a patient who had deep carious lesions in a primary molar. After 5 minutes of application, the soft and infected tissues were removed from the side walls of the cavity and, after, PDT was held in the pulp wall with red laser (660 nm), energy of 30 J, output power of 100 mW and 5 minutes of exposure time. This caused a reduction in the amount of dental tissue removed, what favored the prognosis of the dental element. After a period of 3 months, a control of the case was done and we discovered that the tooth that received the PDT was not painful and the x-ray showed an absence of lesions in the furcation. Conclusion: PDT with PapacárieMblue has been effective in the removal of a deep carious lesion that had a risk of pulp exposure.